Experts' consensus over key components of online learning environments in medical education: a modified e-delphi study - Naeem, Noor i.Kiran; Hadie, Siti Nurma Hanim; Ismail, Irwan Mahazir; Naeem, Zil e.Fatima; Khan, Ahmad Hassan; Yusoff, Muhamad Saiful Bahri (Khyber Medical University, 2025)
Objectives: To achieve expert consensus on the essential components for effective online learning environments in medical education using a modified eDelphi approach. Methods: A purposive sampling strategy was used to recruit 18 professionals from seven countries, including medical educationists, instructional designers, and health professions faculty, all with minimum two years of experience in technology-enhanced learning environments. Two Delphi rounds were conducted online, where experts rated nine components and 25 subcomponents using a 4-point Likert scale for appropriateness and applicability. Statistical analysis included descriptive statistics (mean, standard deviation) and Friedman's non-parametric rank correlation test, with ≥75% agreement set as the consensus threshold. Results: Fifteen out of 18 experts participated (response rate: 83.3%) and evaluated nine components and 24 subcomponents for appropriateness and applicability. Consensus was achieved across all components, with "Institutional Support" (3.6±0.50) and "Digital Capability" (3.6±0.51) receiving 100% agreement, while "Learning Facilitator" had the lowest score (3.2±0.51; 86.7% agreement). Expert feedback led to refinements in definitions and nomenclature, e.g. renaming "Pedagogical Practices" to "Cybergogical Practices" for better conceptual clarity. Friedman test showed no significant differences in rankings (p >0.05), confirming consensus. The finalized framework supports curriculum design, faculty development, and policymaking. Conclusion: Modified e-Delphi study established a consensus-driven framework for optimizing online learning in medical education. By refining key components-Digital Capability, Cognitive Enhancement, and Cybergogical Practices-it enhances clarity in e-learning terminology and supports curriculum design, faculty development, and policymaking. With strong expert agreement, it ensures adaptability in hybrid education while paving the way for future research and innovation.